Key issues and advances in clinical trial design for the treatment of cerebral small vessel disease - ZHU Yi⁃cheng; HAN Fei (Chinese Journal of Contemporary Neurology and Neurosurgery)
Cerebral small vessel disease (CSVD) is a major cause of stroke and dementia, with its treatment paradigm shifting from conventional risk factor management to targeted pathophysiological interventions. This article reviews the current landscape and key challenges in CSVD treatment research, focusing on patient selection, optimization of study endpoints, and development of targeted therapeuticstrategies. Additionally, it explores the FINESSE framework, which aims to refine CSVD clinical trial design and accelerate advancements in treatment.